Ferritic stainless steel with excellent workability
Patent Information
- Application Number
- JP2025060845
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 本発明のフェライト系ステンレス鋼は、レキュペレータに好適な耐熱性に加えて、高温クリープ強度に優れ、かつ、結晶粒粗大化を抑制し靭性を高めることによって、熱間加工性に優れるものとなっている。すなわち、本発明のフェライト系ステンレス鋼は、850℃での高温クリープ試験における破断時間が500時間を超えるなど、高温での優れたクリープ強度を備え、かつ、シャルピー衝撃試験方法に基づく吸収エネルギーが80J/cm2以上と靭性に優れることから熱間加工性に優れている。
Smart Images

Figure 2026167310000001 
Figure 2026167310000002
Abstract
Description
Technical Field
[0001] The present invention relates to a ferritic stainless steel with excellent workability. For example, the present invention relates to a ferritic heat-resistant stainless steel suitable for use in recuperator (recuperative heat exchanger) heat exchangers and other heat exchangers for improving heat balance.
Background Art
[0002] In industrial furnaces such as melting furnaces, heating furnaces and heat treatment furnaces, energy efficiency is improved by reusing the heat of the gas discharged after combustion for preheating combustion air via a waste heat recovery device. A recuperator is a recuperative heat exchanger that reuses the heat of the gas discharged after combustion to preheat the combustion air introduced into the furnace, and the combustion gas and the air to be preheated flow separated by a thin wall, so that the temperature of the steel material used in these devices reaches a maximum of 750°C. Accordingly, heat-resistant steels such as DIN (German Industrial Standard) 1.4762 are used in conventional recuperators.
[0003] To further improve energy efficiency, it is effective to increase the waste heat recovery temperature, and thus a heat-resistant steel that can raise the service environment temperature inside the recuperator to 800°C or higher is demanded. As the service environment temperature increases, the temperature of the steel material also rises to 800°C or higher. Under such a high-temperature environment, there are problems that the wall thinning amount of the steel material increases due to oxidation and corrosion, and the creep strength of the steel material decreases. Accordingly, as a steel material used at a high temperature of 800°C or higher for a recuperator tube, a heat-resistant steel having further improved high-temperature oxidation resistance, sulfur attack resistance and high-temperature creep strength over conventional steel materials is required.
[0004] Therefore, the applicant states that the material contains, by mass%, C: 0.040% or less, Si: 0.40~1.20%, Mn: 0.01~0.50%, P: 0.040% or less, S: 0.030% or less, Cr: 22.50~27.50%, Al: 0.60~1.40%, Ti: 0.10~0.90%, N: 0.0500% or less, and Nb: 0.10~0.90%, and in these chemical components, (Ti / 48 + Nb / 93) - (C / 12 + N / 14): A ferritic stainless steel with excellent high-temperature corrosion resistance and high-temperature creep strength is proposed, characterized by having 0.004-0.025% of the composition, with the remainder being Fe and unavoidable impurities, and the amount of Laves phase precipitated, calculated by image analysis of a specimen photographed with an electron microscope after a creep rupture test at 850°C and 9 MPa, being 0.20 volume fraction (%) or more (see Patent Document 1). However, its processability is not sufficient, and there is room for further improvement.
[0005] Furthermore, conventional heat-resistant steel, Type 429Nb steel (14Cr-0.9Si-0.4Nb steel), is considered insufficient in terms of high-temperature resistance. Therefore, SUS444 steel (18Cr-2Mo-Nb steel), which has an increased amount of alloying elements, is used. However, SUS444 steel has the problem of reduced workability at room temperature and is prone to brittle fracture during processing due to its poor toughness.
[0006] Therefore, the composition is such that, in mass%, C<0.020%, Si≦0.25%, Mn<2.00%, P<0.060%, S<0.008%, Cr:12.0% or more, less than 20.0%, Ni<1.00%, Nb:10×(C+N)% or more, less than 0.80%, N<0.020%, B:0.0005% or more, less than 0.0100%, with the remainder being Fe and unavoidable impurities, and is suitable for any cutting of cold-rolled steel sheets. A ferritic stainless steel with excellent toughness has been proposed, characterized by observing the crystal grains and precipitates appearing on the surface with an electron microscope, calculating the occupancy rate of precipitates on the grain boundaries using formula (1) as the ratio of the length occupied by each precipitate on the grain boundary to the length of the grain boundary, and setting the occupancy rate [Σ(length occupied by each precipitate on the grain boundary) / Σ(length of the grain boundary)] to 0.4 or less (see Patent Document 2). This proposal aims to produce a ferritic stainless steel with excellent toughness and high-temperature strength by controlling the proportion of precipitates on the grain boundaries of the steel. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Patent No. 6644512 [Patent Document 2] Patent No. 5396752 [Overview of the project] [Problems that the invention aims to solve]
[0008] However, all of these proposals tended to result in grain coarsening and cracking during the manufacturing process. For example, the proposal in Patent Document 1 does not actively utilize phosphorus (P), and there is room for improvement in workability. Therefore, the present invention aims to improve the hot workability of ferritic stainless steel, which is a heat-resistant steel, by suppressing grain coarsening and increasing toughness using phosphorus. [Means for solving the problem]
[0009] Since ferritic stainless steels do not undergo phase transformation, microstructure refinement through heat treatment is not possible, and fine grains must be achieved solely through plastic deformation from the solidified structure. Therefore, to prevent grain coarsening during heating, the active use of phosphorus (FeTiP) is considered. However, generally, phosphorus segregates at grain boundaries, reducing the toughness of the material, so the use of phosphorus has not been easy.
[0010] As a result of diligent research, the inventors discovered that by optimizing the balance of Cr, Ti, and P components, it is possible to obtain a heat-resistant steel that suppresses grain boundary fracture while refining the crystal grains and improving toughness and workability. They also found that with such an alloy design, phosphate groups can be appropriately precipitated during the process of forming steel pipes by extrusion molding, thereby maintaining a fine microstructure.
[0011] The first means for solving the problems of the present invention is a ferritic stainless steel consisting of, by mass%, C: 0.04% or less (including 0%), Si: 0.40-1.20%, Mn: 0.01-0.70%, P: 0.025-0.080%, Cr: 22.50-27.50%, Al: 0.60-1.40%, Ti: 0.10-0.90%, with the remainder being Fe and unavoidable impurities, and further satisfying the following formulas 1 and 2. Formula 1: 0.5<13×[P]+[Ti]<1.5 Formula 2: 3.5<(0.85×[Cr]+10.3×[Mo]) / 81×[P]<14.1 However, the values in the brackets [ ] in each formula should be replaced with the mass percentage values of the elemental symbols listed.
[0012] Furthermore, it is more preferable that the P content in such ferritic stainless steel is 0.030 to 0.060%.
[0013] The second method is a ferritic stainless steel that, in addition to the components described in the first method, contains one or two of the following in mass%, Mo: 0.01-1.00% and W: 0.01-1.50%, with the remainder being Fe and unavoidable impurities, and further satisfies the following formulas 1 and 2. Formula 1: 0.5<13×[P]+[Ti]<1.5 Formula 2: 3.5<(0.85×[Cr]+10.3×[Mo]) / 81×[P]<14.1 However, the values in the brackets [ ] in each formula should be replaced with the mass percentage values of the elemental symbols listed. [Effects of the Invention]
[0014] The ferritic stainless steel of the present invention possesses excellent heat resistance suitable for recuperators, as well as superior high-temperature creep strength and excellent hot workability due to suppressed grain coarsening and increased toughness. Specifically, the ferritic stainless steel of the present invention exhibits excellent creep strength at high temperatures, with a fracture time exceeding 500 hours in a high-temperature creep test at 850°C, and an absorbed energy of 80 J / cm based on the Charpy impact test method. 2 Due to its superior toughness and other properties, it exhibits excellent hot workability. [Modes for carrying out the invention]
[0015] Before describing embodiments of the present invention, the reason for specifying the steel composition will be explained. Note that the percentages for chemical composition are in mass percentages.
[0016] C: 0.04% or less While carbon (C) improves creep strength at high temperatures, excessive amounts can reduce oxidation resistance and toughness. Therefore, the amount of C should be 0.04% or less (including 0%).
[0017] Si: 0.40~1.20% Si is a useful component for deoxidation during manufacturing. Insufficient Si can easily lead to inadequate deoxidation during manufacturing, resulting in a decrease in the position of intervening materials. Therefore, Si should be at least 0.40%. On the other hand, since Si increases the hardness of the material, excessive Si can reduce processability and toughness. Therefore, Si should be 1.20% or less.
[0018] Mn: 0.01~0.70% Mn is used as a deoxidizer during steelmaking, and is a component that improves oxidation resistance and scale peeling resistance. Insufficient Mn tends to cause insufficient deoxidation during production, reduces the cleanliness of inclusions, and also lowers oxidation resistance and scale peeling resistance. From these perspectives, the Mn content is set to 0.01% or more. On the other hand, excessive Mn may form an austenite phase and cause initiation points of abnormal oxidation. Since the austenite phase has a larger thermal expansion coefficient than the ferrite phase, it is susceptible to the effects of thermal expansion such as dimensional change when used at high temperatures. Therefore, the upper limit of Mn is set to 0.70%.
[0019] P: 0.025 to 0.080% P is a component that improves strength and workability, and is a component that enhances hot workability by forming phosphides (such as FeTiP), suppressing grain coarsening and increasing toughness. Since ferritic stainless steel does not undergo phase transformation, microstructure refinement by heat treatment cannot be expected, so it is necessary to achieve grain refinement only by plastic working from the solidified structure. The addition of P can suppress grain coarsening caused by recrystallization as the temperature rises. Therefore, the P content is set to 0.025% or more, and preferably 0.030% or more. If P is too low, the strength decreases and workability deteriorates. However, P is a component that easily segregates at grain boundaries and reduces the toughness of the material. Therefore, excessive P promotes grain boundary segregation and tends to lower toughness. Therefore, the P content is set to 0.080% or less, and preferably 0.060% or less.
[0020] Cr: 22.50 to 27.50% Cr is one of the basic components of ferritic stainless steel, which stabilizes the ferrite phase and is an important component for improving oxidation resistance, which is highly valued as a high-temperature material. If Cr is too low, the ferrite phase becomes unstable, the oxidation resistance decreases, and the influence of grain boundary segregation of impurity elements increases. From these perspectives, the Cr content is set to 22.50% or more. Excessive Cr reduces toughness. The Cr content is set to 27.50% or less.
[0021] Al: 0.60 to 1.40% Al is a component with high deoxidizing ability and is used as a deoxidizing agent in steelmaking. It also improves high-temperature oxidation resistance by forming a dense oxide film on the surface in high-temperature oxidizing environments. If the amount of Al is insufficient, it is likely to lead to inadequate deoxidation during manufacturing, a decrease in the position of intervening materials, and a failure to form an oxide film, resulting in a decrease in high-temperature oxidation resistance. Therefore, the amount of Al should be 0.60% or more. On the other hand, if the amount of Al is excessive, the toughness and workability of the steel will decrease. Therefore, the amount of Al should be 1.40% or more.
[0022] Ti: 0.10~0.90% Ti is a component that improves high-temperature strength and generates phosphate compounds. If the amount of Ti is insufficient, the high-temperature strength will be insufficient, phosphate compounds will be insufficient, and the crystal grains will coarse. Therefore, the amount of Ti should be 0.10% or more. On the other hand, if the amount of Ti is excessive, the processability will deteriorate and the cost will increase due to the component. Therefore, the amount of Ti should be 0.90% or less.
[0023] Mo and W are optional additional components in this invention, and one or two of them may be added.
[0024] Mo: 0.01~1.00% Mo is a component that contributes to improving high-temperature tensile properties, strength, and oxidation resistance. Furthermore, it significantly increases the effect of segregation of impurity elements. Therefore, it is preferable to contain Mo at a concentration of 0.01 to 1.00%. However, adding excessive amounts of Mo increases costs and leads to grain coarsening, reducing toughness and workability. Therefore, when adding Mo, it is preferable to keep the concentration below 1.00%.
[0025] W: 0.01~1.50% Water (W) is a component that can improve high-temperature strength and oxidation resistance. However, excessive amounts of W can reduce processability. Therefore, when adding W, it is preferable to keep the amount to 1.50% or less.
[0026] Remainder: Fe and unavoidable impurities The remainder consists of Fe and unavoidable impurities.
[0027] S: (Unavoidable impurities) Preferably 0.030% or less Although sulfur (S) is an unavoidable impurity, an excess of S leads to the formation of large amounts of coarse MnS, resulting in a decrease in toughness and fatigue strength. Therefore, it is preferable that the S content be 0.030% or less.
[0028] N: (Unavoidable impurities) Preferably 0.030% or less Nitrogen (N) is an unavoidable impurity, and while it generates fine carbonitrides, excess N leads to the formation of coarse carbonitrides, reducing toughness and fatigue strength. Therefore, N content of 0.030% or less is preferable.
[0029] Formula 1: 0.5<13×[P]+[Ti]<1.5 Adding phosphorus (P) can suppress grain coarsening due to recrystallization as the temperature rises, but P tends to segregate at grain boundaries, which can reduce the toughness of the material. Therefore, the balance of components is important. In this regard, Equation 1 is an index defined in consideration of the component balance required to appropriately generate phosphides (FeTiP) for recrystallization suppression. If the value obtained by substituting the mass percentage values of P and Ti into the brackets [ ] in Equation 1 is greater than 0.5 but less than 1.5, then Equation 1 is satisfied, and grain coarsening due to recrystallization is suppressed.
[0030] Formula 2: 3.5<(0.85×[Cr]+10.3×[Mo]) / 81×[P]<14.1 Since phosphorus (P) tends to segregate at grain boundaries, which can reduce the toughness of the material, Equation 2 is an indicator for balancing phosphorus with other components (Cr and Mo) to reduce grain boundary segregation. If the value obtained by substituting the mass percentage values of P, Cr, and Mo into the brackets of Equation 2 is greater than 3.5 and less than 14.1, then Equation 2 is satisfied, and grain boundary segregation can be reduced.
[0031] Embodiments of the present invention are described below. First, 100 kg of steel consisting of the components shown in Table 1, Invention Steels 1-15 and Comparative Examples 1-9, with the remainder being Fe and unavoidable impurities, was melted in a vacuum melting furnace. Next, it was heated to 1100°C and forged to produce a 15 mm diameter steel bar. After that, it was heat-treated at 1100°C for 15 mins and then water-cooled.
[0032] [Table 1]
[0033] [Table 2]
[0034] <Evaluation Criteria> The following items were evaluated to assess the balance between high-temperature strength and processability. (1) Creep strength at high temperatures Evaluation of fracture time under a tensile stress load of 9.0 MPa at 750°C. (2) Charpy impact test Evaluation of processability based on toughness assessment using absorbed energy
[0035] <Evaluation Method> (1) Creep test For each inventive steel and comparative steel, creep test specimens with a parallel section diameter of 6 mm were prepared based on the creep test specimens specified in JIS (Japanese Industrial Standards) Z2271. Using these prepared creep test specimens, a tensile stress of 9.0 MPa was applied at 750°C, and the time until fracture was measured. Specimens with a fracture time exceeding 500 hours were evaluated as having superior high-temperature creep strength and are indicated with a circle (○) in Tables 1 and 2. On the other hand, specimens with a fracture time of 500 hours or less were evaluated as having inferior high-temperature creep strength and are indicated with a cross (×).
[0036] (2) Charpy impact test For each inventive steel and comparative steel, 2mm-V notch test specimens were prepared in accordance with the Charpy impact test method for metallic materials specified in JIS Z2242. These prepared 2mm-V notch test specimens were heated at 100°C for 10 minutes, then fractured with a hammer, and the absorbed energy was measured. The absorbed energy based on the Charpy impact test method was 80 J / cm². 2 The above materials were evaluated as having excellent toughness and are indicated with the symbol ○ in Tables 1 and 2.
[0037] Inventive steels 1 to 15 are all ferritic stainless steels satisfying the component composition and formulas 1 and 2 described in the means of the present invention. In high-temperature creep strength tests, the fracture times for all of them exceeded 500 hours, demonstrating excellent high-temperature strength. Furthermore, the results of Charpy impact tests ranged from 87 to 257 J / cm². 2 It was confirmed that it exhibits excellent toughness and also has excellent processability.
[0038] Therefore, the ferritic stainless steel of the present invention is a heat-resistant steel with appropriate strength even when applied as a steel material in high-temperature environments of 800°C or higher, such as in recuperators, and possesses toughness that makes it less susceptible to brittle fracture during processing.
[0039] Comparative Example 1 has an insufficient amount of P, and the value of Equation 2 falls above the upper limit, failing to satisfy the condition. As a result, it has low toughness and poor machinability. Comparative Example 2 has an excess of P, which promotes grain boundary segregation and reduces toughness. Comparative Example 3 has an excess of Si and Mo, and the value of Equation 2 is outside the upper limit, resulting in low toughness and poor machinability. Comparative Example 4 has an insufficient amount of Cr, resulting in poor high-temperature creep strength, making it unsuitable as a high-temperature material. Comparative Example 5 has an excessive amount of Al, resulting in low toughness and poor machinability. Comparative Example 6 does not satisfy the value of Equation 1, as it falls below the lower limit, resulting in poor high-temperature creep strength, low toughness, and poor processability. Comparative Example 7 does not satisfy the value of Equation 1, as it falls above the upper limit, resulting in low toughness and poor machinability. Comparative Example 8 does not satisfy the value of Equation 2, as it falls below the lower limit, resulting in low toughness and poor machinability. Comparative Example 9 does not satisfy the value of Equation 2, as it falls above the upper limit, resulting in low toughness and poor machinability.
Claims
1. In mass percent, C: 0.04% or less (including 0%) Si: 0.40-1.20%, Mn: 0.01 to 0.70%, P: 0.025-0.080%, Cr: 22.50-27.50%, Al: 0.60-1.40%, Ti: 0.10-0.90%, The remainder consists of Fe and unavoidable impurities. Furthermore, a ferritic stainless steel that satisfies the following equations 1 and 2. Formula 1: 0.5<13×[P]+[Ti]<1.5 Formula 2: 3.5<(0.85×[Cr]+10.3×[Mo]) / 81×[P]<14.1 However, the values of the mass percentage of the elemental symbol listed in each formula should be substituted into the brackets [ ].
2. In addition to the components of claim 1, the material contains one or two of the following in mass%, Mo: 0.01 to 1.00% and W: 0.01 to 1.50%, with the remainder being Fe and unavoidable impurities. Furthermore, a ferritic stainless steel that satisfies the following equations 1 and 2. Formula 1: 0.5<13×[P]+[Ti]<1.5 Formula 2: 3.5<(0.85×[Cr]+10.3×[Mo]) / 81×[P]<14.1 However, the values of the mass percentage of the elemental symbol listed in each formula should be substituted into the brackets [ ].
Citation Information
Patent Citations
Voltage subtractor for seriessparallel ad converter
JP1978096752A
Ferritic stainless steel with excellent high-temperature corrosion resistance and high-temperature creep strength
JP6644512B2